Why working conditions are a key issue of sustainability in agriculture? A comparison between agroecological, organic and conventional vegetable systems. (November 2017) - Dumont, Antoinette M.; Baret, Philippe V.
Abstract: This study investigates whether 'green jobs' in agriculture could contribute to better working conditions. We examine a sample of 41 conventional, organic and agroecological vegetable producers who provide fresh produce for markets exploring their working conditions and the employment conditions of their workers, in Wallonia (Belgium). Drawing on the sociological, economic and agricultural literature, we identify nine dimensions that determine working conditions: leeway and control level; income and social benefits; work (in)security; political experience at work; time at work; intrinsic benefits of work; work-related discomfort; occupational health; and competence. We also assess the employment contracts of workers and the way producers manage their workers. Overall we identify four key issues. First, working conditions were not necessarily better for producers in systems that put more emphasis on ecological values. The socio-economic viability of three production systems, including agroecological market gardening on small areas of land, is insufficient. Second, workers in all systems, except in one agroecological system, experience poor employment conditions. Third, each group of producers has to make trade-offs between the ecological, societal and economic dimensions of their business. Finally, we note that socio-economic and political context, history, work orientation and socio-cultural heritage have more influence on producers' working conditions than their degree of mechanization. Highlights: A theoretical framework based on the socioeconomic and agricultural literature, is proposed to study working conditions. The working conditions are not necessarily better for producers and workers in systems with the strongest ecological value. One agroecological system offers one of the best work experiences while another offer one of the most difficult.